Efektivitas Terapi Musik Alam terhadap Tingkat Kecemasan pada Pasien Hemodialisis - Wiyanna Mathofani Siregar; Dudut Tanjung; Elmeida Effendy (Journal of Telenursing (JOTING), 2022)
This study aims to identify and evaluate the effect of natural music therapy intervention on hemodialysis patients. This research uses quantitative methods with a quasi-experimental non-equivalent control group pretest-posttest design. Respondents in this study were 96 hemodialysis patients. Data were collected using a State Anxiety Inventory (SAI) questionnaire comprising 20 statement items. Data were analyzed using nonparametric tests (Wilcoxon Signed Rank Test and Mann Whitney U Test). The results showed a difference between the mean value of anxiety in the intervention group and the control group, namely 37.90 in the intervention group and 42.33 in the control group, with a p-value of 0.048. In conclusion, natural music therapy is recommended as an alternative to reduce the level of anxiety in hemodialysis patients to improve the patient's quality of life. Keywords: Hemodialysis, Anxiety, Natural Music Therapy